Against citizenship : the violence of the normative - Brandzel, Amy L., 1970- (Dissident feminisms., 2016)
"Numerous activists and scholars have appealed for rights, inclusion, and justice in the name of "citizenship." Against Citizenship provocatively shows that there is nothing redeemable about citizenship, nothing worth salvaging or sustaining in the name of "community," practice, or belonging. According to Brandzel, citizenship is a violent dehumanizing mechanism that makes the comparative devaluing of human lives seem commonsensical, logical, and even necessary. Against Citizenship argues that whenever we work on behalf of citizenship, whenever we work toward including more types of peoples under its reign, we inevitably reify the violence of citizenship against nonnormative others. Brandzel's focus on three legal case studies--same-sex marriage law, hate crime legislation, and Native Hawaiian sovereignty and racialization--exposes how citizenship confounds and obscures the mutual processes of settler colonialism, racism, sexism, and heterosexism. In this way, Brandzel argues that citizenship requires anti-intersectionality, that is, strategies that deny the mutuality and contingency of race, class, gender, sexuality, and nation--and how, oftentimes, progressive left activists and scholars follow suit. Against Citizenship is an impassioned plea for a queer, decolonial, anti-racist coalitional stance against the systemized human de/valuing and anti-intersectionalities of citizenship."--Publisher's website